1998
DOI: 10.1038/eye.1998.251
|View full text |Cite
|
Sign up to set email alerts
|

Inferior oblique syndrome: An under-recognised complication of strabismus surgery

Abstract: Purpose To show the predictive factors that would indicate the possibility of inferior oblique inclusion when considering surgery on a previously operated lateral rectus muscle. We also aim to highlight the importance of freeing any inferior oblique attachment to the lateral rectus muscle during either a resection or a recession procedure. Methods A retrospective review was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In these cases strabismus surgery to free the IO fibers often fails to reduce the vertical deviation. 5 One patient was noticed to have 2 lateral rectus tendon heads separated from each other; one at the original site of insertion and one at the recessed position. In this case the anterior tendon head was isolated on a separate tendon hook after clearing the connective tissue, which was then recessed along with the posterior tendon insertion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases strabismus surgery to free the IO fibers often fails to reduce the vertical deviation. 5 One patient was noticed to have 2 lateral rectus tendon heads separated from each other; one at the original site of insertion and one at the recessed position. In this case the anterior tendon head was isolated on a separate tendon hook after clearing the connective tissue, which was then recessed along with the posterior tendon insertion.…”
Section: Resultsmentioning
confidence: 99%
“…8 This period allows time for recovery of the muscle function and improvement in ductions but prevents significant contracture. 5 Surgery on a slipped muscle involves forced duction testing, clearing the surrounding connective tissue from the muscles, and measuring the exact location of all the muscles concerned. A definitive diagnosis is made intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In the current study, 45 patients were found to have a significantly reduced vertical deviation resulting from released IO muscle inclusion. This correction has been stable for a follow-up period of 2 to 10 years without recurrence of the previous amount of vertical deviation.…”
Section: Discussionmentioning
confidence: 87%
“…Reoperation on a patient within 10 days of the original surgery prevents contracture of the lost muscle. 3,7 In our case series, cases 1 and 2 underwent reoperation 1 day after the previous surgery. Case 3 underwent reoperation 1 week after the initial surgery.…”
Section: Discussionmentioning
confidence: 95%